Refining information literacy practice: Examining the foundations of information literacy theory. (June 2020) - Flierl, Michael; Maybee, Clarence
There are many ways for an academic librarian to contribute to the teaching and learning mission of an institution ranging from direct instruction to assignment design. Given this plethora of information literacy educational practices, what should academic librarians and educators focus time, labor, and resources on, and why should they do so? With an eye towards improving information literacy educational practice and addressing these fundamental questions, we examine the foundational philosophical commitments of two information literacy theories, Critical Information Literacy and Informed Learning. We find that these information literacy theories may be biased towards a 20th-century European worldview. This finding supports the idea that "good" IL educational practice in higher education requires active engagement with information literacy theory to justify what one does as an educator and to demonstrate why information literacy can be integral to learning in higher education.